CAPITAL FLOWS, MONEY SUPPLY AND PROPERTY PRICES IN CHINA - TAGUCHI, Hiroyuki; TIAN, Lina (Theoretical and Practical Research in Economic Fields; Vol 8 No 2 (2017): TPREF, Volume VIII, Issue 2(16), Winter 2017DO - 10.14505/tpref.v8.2(16).01, 2017)
This article examines the interaction among capital flows, money supply and property prices with a focus of Chinese economy by using a vector auto-regression (VAR) estimation as an analytical framework. The key research questions were, first, whether money supply has been determined independently from capital flows, and then which factor, capital flows or money supply, has given a dominant effect on property prices. The contributions of this study are to investigate the impacts on property prices jointly from capital flows as an external factor and from money supply as a domestic factor, and to count on the differences in the trends in property prices of seventy regional cities in China. The main findings through the VAR estimations were as follows. First, domestic money supply has been determined exclusively from external capital flows through the authority’s perfect sterilization of foreign-exchange-market intervention. Second, the main contributor to property prices’ movement has been domestic money supply rather than external capital flows. Third, some deviations of property prices from the trend in money supply were found in big cities and/or coastal advanced cities.